VD_FINDINFO HC / 2012 / 599 vom 3. September 2012 - VD Tribunal cantonal (2012)
PROPRIÉTÉ, ACTION EN CESSATION DE TROUBLE, ABUS DE DROIT, CONDUITETUYAU | 2 al. 2 CC, 641 al. 2 CC, 667 al. 1 CC, 308 CPC (CH)